2017
DOI: 10.1002/wsb.785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acoustic recorders and field observers for monitoring tundra bird communities

Abstract: Acoustic recorders can be useful for studying bird populations but their efficiency and accuracy should be assessed in pertinent ecological settings before use. We investigated the utility of an acoustic recorder for monitoring abundance of tundra‐breeding birds relative to point‐count surveys in northwestern Alaska, USA, during 2014. Our objectives were to 1) compare numbers of birds and species detected by a field observer with those detected simultaneously by an acoustic recorder; 2) evaluate how detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…However, there was no such effect in the study by Vold et al. () based on the number of detections in the different distance bins, although the visual‐only detections could have offset an avoidance effect. In other studies (Hutto & Stutzman, ), no clear avoidance effect could be seen in histograms of detection distances excluding visual‐only detections.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, there was no such effect in the study by Vold et al. () based on the number of detections in the different distance bins, although the visual‐only detections could have offset an avoidance effect. In other studies (Hutto & Stutzman, ), no clear avoidance effect could be seen in histograms of detection distances excluding visual‐only detections.…”
Section: Discussionmentioning
confidence: 79%
“…Previous comparisons have thus far failed to find systematic habitat related differences in counts between recorders and humans (Celis‐Murillo et al., ; Van Wilgenburg et al., ) despite there being known differences in sound attenuation (Yip et al., ). It is probable that aural detectability in point counts and sound recordings are similarly affected by habitat and thus introduce no bias in our comparisons owing to the nature of the paired comparisons (Van Wilgenburg et al., ; Vold et al., ). Moreover, our analyses correcting for detection ranges implicitly accounts for the habitat effect on sound detection range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vold et al. () showed that even in tundra bird communities, visual obstruction was not associated with detected bird abundance. In more heterogeneous montane habitats, McGrann and Furnas () detected only 1% of birds just visually and in forest, Darras et al.…”
Section: Comparison Of Survey Methodsmentioning
confidence: 99%
“…It follows that any comparison of point counts vs. sound recordings with regard to variables like abundance or species richness is biased if the differing detection ranges are not taken into account (Darras et al., ; Yip, Bayne, Sólymos, Campbell, & Proppe, ), as these variables increase with the sampled area. Indeed, it has been suggested recently that the differing effective detection ranges may cause the discrepancy in richness values between point counts and sound recorders (Van Wilgenburg et al., ; Vold, Handel, & Mcnew, ). However, so far bird species richness values were used as measure to compare the sampling efficiency of point counts vs. autonomous sound recorders in several studies (Shonfield & Bayne, ).…”
Section: Introductionmentioning
confidence: 99%